2020
DOI: 10.1039/c9ra09318d
|View full text |Cite
|
Sign up to set email alerts
|

Nickel oxide decorated MoS2nanosheet-based non-enzymatic sensor for the selective detection of glucose

Abstract: This study reported that NiO/MoS2 based nanocomposite can be used as an electrocatalytic material to detect glucose with high selectivity in a blood serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…A similar sensing mechanism has been proposed for the non-enzymatic detection of glucose, achieved via its catalytic oxidation using NiO-decorated MoS 2 . [50] In our study, for such purpose Pt might be a suitable doping material, given its strong reactivity towards the carbonyl group of cortisol: as previously discussed, we found this metal element to donate a significant amount of charge to C-3, which leads to the strongest weakening of the C=O double bond. In addition to single-atom doping, decorating MoS 2 surface with Pt nanoparticles may be a viable alternative that could be explored.…”
Section: Sensing Mechanismssupporting
confidence: 66%
“…A similar sensing mechanism has been proposed for the non-enzymatic detection of glucose, achieved via its catalytic oxidation using NiO-decorated MoS 2 . [50] In our study, for such purpose Pt might be a suitable doping material, given its strong reactivity towards the carbonyl group of cortisol: as previously discussed, we found this metal element to donate a significant amount of charge to C-3, which leads to the strongest weakening of the C=O double bond. In addition to single-atom doping, decorating MoS 2 surface with Pt nanoparticles may be a viable alternative that could be explored.…”
Section: Sensing Mechanismssupporting
confidence: 66%
“…Controlling the interactions of enzymes with the substrate to improve electron transfer processes remains a challenge that causes a substantial loss of GOx activity, leading to poor overall performance of the sensor. Therefore, other researchers saw an opportunity to explore various 2D MoS 2 /metal-NS composites (Ni-MoS 2 [ 35 ], CuO-MoS 2 [ 82 ], Cu-MoS 2 [ 85 ], Au-Pd/MoS 2 [ 89 ], Cu 2 O-MoS 2 [ 93 ], NiO-MoS 2 [ 103 ], NiCo 2 O 4 -MoS 2 [ 108 ], and MoS 2 -PPY-Au [ 206 ]) as electrode materials to construct non-enzymatic sensors due to their extraordinary electrocatalytic activities, excellent conductivity, and large surface areas. The experimental results revealed that the performances of all these 2D MoS 2 /metal-NS composites were remarkable, as shown in Table 2 .…”
Section: Application Of 2d Mos 2 -Based Nanocompos...mentioning
confidence: 99%
“…Enzymatic electrochemical sensors are vulnerable to the environmental factors such as temperature, pressure, pH, and biological pathogens [20]. The abovestated problems can be neglected by using nonenzymatic electrochemical sensors [21]. Majumder et al reported a nonenzymatic electrochemical sensor for H 2 O 2 and hydrazine using 3D microsnowflake architectures of α-Fe 2 O 3 [22].…”
Section: Introductionmentioning
confidence: 99%